The Role of Industry 4.0 and Digitalization in agriculture, Especially in Romanian Agriculture - Nagy, Szeréna (International Journal of Engineering and Management Sciences, 2022)
The use of robotics, automation, big data, artificial intelligence are growing in the world and in the agricultural sector, which contribute to the development of a more efficient agricultural sector. In the agriculture sector for sustainable development it is necessary the use of opportunities and technologies provided by industry 4.0. For the agriculture sector digitalization means the future, because it helps increasing output meanwhile environmental pressure is remitting, and is not increasing. The aim of these paper is to present the concept of Industry 4.0 in agriculture and to analyse the romanian agricultural sector attitude and conditions towards digitalization.